EXTRACTING VALUE ADDED COMPOUNDS FROM CITRUS RECYCLING WATER - Khumora Abdashimova; Sattarov Karim Qarshievich; Oktamova Charos (Journal of new century innovations, 2023)
Abstract: Demand for food products, History of citrus fruits, Processing of citrus fruits, Creation of environmentally friendly technologies, Advantages of citrus canning industry